The ethnic-racial and gender debate in Social Work training in the North Region - Barroso, Milena Fernandes; Martins, Ana Claudia Lopes; Cavalcante Rodrigues, Taysa (Argumentum, 2024)
The article deals with the inclusion of the ethnic-racial and gender debate in professional training in Social Work. With the aim of understanding the insertion of these themes in the pedagogical projects of courses in the northern region of the country, a bibliographical and documentary research was carried out at federal universities, focusing on the analysis of disciplines, syllabi, research and university extension. The text highlights advances and challenges for the inclusion and consolidation of these themes in the training of social workers. There is an expansion of the debate in the category as a whole, however, in undergraduate training, such issues still do not assume centrality, they appear in mandatory subjects in a diffuse and punctual manner and in some optional subjects that deal with the themes.